Genetic Identity And Affiliation - del Águila Tuesta, Frieda Roxana (2015)
This article shows the importance of advances in medical science whose success has solved the problem of infertility using the Assisted Human Reproduction Techniques; but also, shows the problems arising as a result of inadequate regulation or biased decisions of the courts that tend to support their position on constitutional principles such as the right to procreation favoring users, protection of personal data contributors (donors), understanding mistakenly give quality and consistent biological child legal relationship to those born with genetic contribution from third parties, protects their fundamental rights; situation which we believe prevents access to know their origins, their inherited genetic truth is basis for its existence and therefore of vital importance in his life and ensuring the proper development of personality, as an inherent element of the right.In these circumstances it necessary to rethink approach based on a natural law that prevents the utilitarianis